2018
DOI: 10.1016/j.bonr.2018.09.002
|View full text |Cite|
|
Sign up to set email alerts
|

A moderate form of osteogenesis imperfecta caused by compound heterozygous LEPRE1 mutations

Abstract: Osteogenesis imperfecta (OI) is a genetic disorder causing skeletal fragility, multiple fractures, and other extraskeletal manifestations. Most cases are caused by mutations in COL1A1 or COL1A2. Recent investigations have discovered several other autosomal recessive genes responsible for OI. Among these genes is LEPRE1, which is involved in post-translational modifications of collagen. To date, more than 40 LEPRE1 mutations have been described. One of these mutations is carried by 1.5% of West Africans and 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…LEPRE1 gene variants are perinatally lethal and severe, presenting as OI types II and III (Santana, Franzone, McGreal, Kruse, & Bober, 2018). We have identified two novel homozygous duplications, c.2131dup (p.Leu711Profs*19)(SCV000987189) and c.1980dup (p.Val661Serfs*33)(SCV000987190), producing a truncated protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LEPRE1 gene variants are perinatally lethal and severe, presenting as OI types II and III (Santana, Franzone, McGreal, Kruse, & Bober, 2018). We have identified two novel homozygous duplications, c.2131dup (p.Leu711Profs*19)(SCV000987189) and c.1980dup (p.Val661Serfs*33)(SCV000987190), producing a truncated protein.…”
Section: Discussionmentioning
confidence: 99%
“…The joint contractures were mainly in FKBP10 variants with isolated cases in BMP1, CRTAP, COL1A1, and COL1A2. The plot was generated using GenVisR Bioconductor package [Colour figure can be viewed at wileyonlinelibrary.com] LEPRE1 gene variants are perinatally lethal and severe, presenting as OI types II and III (Santana, Franzone, McGreal, Kruse, & Bober, 2018). We have identified two novel homozygous duplications, c.2131dup (p.Leu711Profs*19)(SCV000987189) and c.1980dup (p.Val661Serfs*33)(SCV000987190), producing a truncated protein.…”
Section: F I G U R Ementioning
confidence: 99%
“…Although the measurements were made using different equipment in different centers, a good response was obtained with >300% improvement. 10 Takagi et al also reported an OI type VIII case in which pamidronate treatment was started at 2 months of age. The patient developed very few fractures and presented a good response.…”
Section: Discussionmentioning
confidence: 98%
“…Moderate type 4 OI has been reported in cases of missense P3H1 variants; numerous cases were documented in Turkish and other OI cohorts [ 7 , 16 ]. Although it is tempting to assume that maintenance of protein expression can have a protective role in diminishing disease severity, it is important to note that missense P3H1 pathogenic variants have also been reported as a cause of type 3 OI [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Defects in collagen type I can also be caused by several genes affecting its regulation [ 4 ]; the prevalence of OI forms by recessive genes may be increased in isolated consanguineous populations [ 5 ]. Pathogenic variants in the prolyl 3-hydroxylase 1 ( P3H1 , OMIM#: 610339) gene were discovered in 2006 as a cause of severe recessive OI, genetic type VIII (OMIM#: 610915) [ 3 , 6 ]; although the clinical types 2 and 3 OI are commonly reported, milder cases also exist [ 7 ]. P3H1 codes for P3H1, which forms a heterotrimeric complex with the cartilage-associated protein (CRTAP) and cyclophilin B (PPIB); pathogenic variants in both of the latter are also associated with OI [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%